Investigação da ativação redox e de interações supramoleculares : o caso da bergenina e de nitroaromáticos substituídos - Vasconcelos, Camila Calado de (2015)
There is a strong interest in phenolic compounds and nitrocompounds in the function of their diverse and significant biological activities. Such compounds can participate in electron transfer reactions and produce metabolites that influence the redox state at the cellular level, with consequent effect on vital biochemical processes. This work aimed to determine the electrodic mechanism involved in the oxidation of bergenin and the reduction of nitrobenzyl derivatives and to evaluate possible supramolecular interactions of bergenin with β-cyclodextrin (β-CD) and deoxyribonucleic acid (DNA) in order to increase its solubility in aqueous medium and help in understanding the molecular mechanism of biological action. The electrochemical studies in protic and aprotic medium were performed in potentiostat PGSTAT302 (AUT 73222) from Autolab® using voltammetric techniques. The influence of the interaction of different cyclodextrins on the solubility of bergenin in aqueous medium was verified through the phase transfer study by cyclic voltammetry. The bergenin:β-CD complex was prepared in 1:1 and 1:2 proportions by the coevaporation technique and characterized by spectroscopic techniques. The theoretical studies were performed through the Gaussian program 09. Bergenin in the free and complexed form were evaluated against antioxidant capacity (lipid peroxidation assays), cytotoxicity (cell viability versus macrophages), and interaction with estimated DNA through the use of dsDNA (double strand) electrochemical sensor and with ssDNA (single strand) for UV-Vis spectrophotometry in solution. The electrochemical results obtained for bergenin demonstrated that its oxidation mechanism in aprotic and protic environments involves, respectively, loss of 1e-/1H+ and 2e-/2H+, when using a glassy carbon electrode. Theoretical data contributed to clarify that oxidative mechanisms involve phenolic hydroxyls. The antioxidant activity of bergenin in the lipoperoxidation inhibition assays was favored in its complexed form with β-CD 1:1. The cytotoxicity of bergenin evaluated in macrophages was also influenced by interaction with β-CD. The electrochemical studies involving ssDNA demonstrated interaction between bergenin and the constituent bases of DNA, suggesting a possible mechanism of biological action. However, the dsDNA biosensor studies showed no interaction. Investigation of the interaction with dsDNA through UV-Vis spectrophotometry resulted in a binding constant between DNA and bergenin in the free and complexed form on the order of 103 and 104 M-1, respectively. The electrochemical behavior of the nitrobenzyl derivatives obtained in aprotic medium presented a voltammetric profile of great complexity, involving patterns related to autoprotonation and dissociative electron transfer reactions. The order of ease of reduction, based on values of first wave reduction potential, was found: ANB > EANBEN > EANB > AANB > ANOH > ATN = ENF > ANBNa > ENM > ANF, obtaining a positive correlation between the compounds with (less negative) with more pronounced biological activity (leishmanicidal and antitumor activities), already described in the literature, which justifies the importance of the electrochemical investigation of bioactive compounds as a tool in medical chemistry, in processes related to the transfer of electrons.